2015
DOI: 10.1002/prep.201500206
|View full text |Cite
|
Sign up to set email alerts
|

Ignition Characteristics of Micro‐Energy Semiconductor Bridges with Different Ignition Compositions

Abstract: [a] 1IntroductionSemiconductor bridges (SCB), whose basic principle is producing heat or plasmat oi gnite energeticm aterials under the stimulation of electric energy, are one of the most important ignition components manufacturedb ym icroelectronics integrationt echnology,a nd has been widely employed in recent years [1][2][3].I ti sa lso conceivable to lower SCB ignitionv oltage by focusingo nt he core technology development of MEMS fuse, that is, to research and develop micro-energy SCB.N evertheless, SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Suitable oxidants can improve the combustion efficiency of such systems by releasing more energy during the decomposition under a continuous oxygen supply. As a result, oxidant mixing has been proposed as an effective way to improve the energy release of the metal fuels in a solid powder form 1–5 .…”
Section: Introductionmentioning
confidence: 99%
“…Suitable oxidants can improve the combustion efficiency of such systems by releasing more energy during the decomposition under a continuous oxygen supply. As a result, oxidant mixing has been proposed as an effective way to improve the energy release of the metal fuels in a solid powder form 1–5 .…”
Section: Introductionmentioning
confidence: 99%
“…In such devices, zirconium potassium perchlorate (ZPP), boron potassium nitrate (BKNO 3 ), and titanium hydride potassium perchlorate (THPP) are used as propellants (or pyro-initiators) 24 . These three types of propellants must have long-term stability to be utilized in practical applications 5 .…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in the Introduction, many researchers consider that heat, via heat-transfer or heat-convection, to be the main energy source of SCB plasma ignition [3]. However, two unusual phenomena were found in our study, which prove that there exist effects in SCB plasma ignition that are not due to heat.…”
Section: Non-heat Effect In Scb Plasma Ignitionmentioning
confidence: 41%
“…SCBs have been used widely in the field of energetic materials due to their rapid response, repeatability and safety [1,2]. The development of SCBs is regarded as the most important milestone in the revolution and development of igniter devices [3]. Much research has been reported regarding the SCB plasma ignition mechanism, in which heating effects are predominant: for example, the micro-convective heating model [4], the heat transfer simulation [5] and the temperature distribution analysis of the silicon bridge [6].…”
Section: Introductionmentioning
confidence: 99%